The use of glucocorticoids in Behçet’s disease - Deniz, Rabia; Bes, Cemal (Acta Medica, 2024)
Behçet’s disease (BD) is a chronic, multifactorial inflammatory disorder characterized by episodic involvement of multiple systems, including mucocutaneous, ocular, vascular, gastrointestinal, joint, and neurological domains. Glucocorticoids (GC) play a pivotal role in managing BD, especially during acute flares and severe organ involvement. This review highlights the tailored use of GC across various manifestations of BD. For mucocutaneous lesions, topical GC are effective, where as short-term low-dose systemic GC are reserved for colchicine-resistantcases. In ocular BD, systemic GC are in dispensable for sight-threatening conditions, often combined with disease-modifying anti-rheumatic drugs (DMARDs) or biologics to minimize GC dependency. In vascular involvement, particularly pulmonary artery aneurysms, high-dose or pulse GC are essential to control vessel wall inflammation, often alongside immunosuppressive agents like cyclophosphamide. Neurological BD necessitate surgent high-dose GC therapy, complemented by DMARDs for sustained control. Joint involvement can be managed with intraarticular GC, reducing systemic exposure. In gastrointestinal BD, GC use is limited due to potential mucosal irritation, with biologics and DMARDs serving as adjunctive options. Across all manifestations, GC tapering is prioritized to mitigate adverse effects, while combination therapy with DMARDs or biologics ensures comprehensive disease control. This comprehensive review underscores the critical role of GC in BD management, advocating for individualized treatment strategies to balance efficacy and safety.